Improving the ability to review preoperative radiographs intraoperatively in trauma and orthopaedic theatres at Lancashire teaching hospitals. Issue 2 (12th October 2017) - Jump, Christopher
Abstract : Background: The ability to review preoperative radiographs during trauma and orthopaedic surgery is essential for the surgeon to provide optimum treatment to the patient. However, due to current information technology (IT) systems, screen-savers frequently interrupt the ability to review images and theatre staff are not routinely available to deactivate the screen-saver. This prolongs theatre time for the patient and affects the quality of care provided. The aim of this quality improvement project was to improve the availability of radiographs for the surgeon to review intraoperatively. Method/results: Data were collected from all trauma and orthopaedic theatres at two hospital sites covering all subspecialties and including emergency and elective cases. Baseline measurements showed that the frequency of preoperative radiographs not interrupted during an operation was 0% (0/50). Following this the Trust's IT systems were improved to prevent activation of the screen-saver on the theatre computers using the generic theatre login details. After the first-cycle intervention, data were collected showing 52% (14/27) of preoperative radiographs were not interrupted by a screen-saver. The cause for this result being less than expected was investigated and found to be due to an alternative computer login being used on the theatre computers at one of the hospital sites. Education of theatre staff was then undertaken to ensure the correct theatre login was used and notices to remind staff placed on the theatre computers. After the second-cycle intervention, data were collected showing that 100% (26/26) of preoperative radiographs were not interrupted during operative time allowing the surgeon to review images when required. Conclusion/implications: This quality improvement project has made changes to theatre IT systems and practices of theatre staff which has resulted in a significant improvement in the ability for the operating surgeon to review preoperative radiographs intraoperatively.